Driving Factors Behind the Adoption of Improved Technologies by Lentil Growers in West Bengal - Dhehibi, Boubaker; Chatterjee, Soumitra; Hazra, Soumavho; Karak, Sabyasachi; Nath, Rajib; Sarker, Ashutosh (International Center for Agricultural Research in the Dry Areas, 2022)
Over the last six decades in India, there has been an unsatisfactory gain in pulse productivity, which is a severe threat to the creation of resilient livelihoods and the overall food and nutritional security of the country. To specifically enhance lentil productivity under rice-based cropping systems in West Bengal, the International Centre for Agriculture Research in the Dry Areas (ICARDA) began a multi-disciplinary project in 2012/13 providing improved technologies, including 29 improved lentil varieties, and a package of agronomic practices to farmers.